Antimicrobial activity of Cymbopogon Species against Human Pathogens and Molecular Characterization by RAPD Markers - P, Prasad M.; Shekhar, Sushant (Asian Journal of Biological and Life Sciences, 2013)
Cymbopogon is a tall perennial grass and shows a great potential for antimicrobial compound against microorganisms. In this study the extracts of three different species of Cymbopogon (C. martinii, C. citratus and C. nardus) was tested against four pathogens (Salmonella sp., Klebsiella sp., Staphylococcus sp. and Enterobacter sp.). All the pathogenic microorganisms were isolated from clinical samples and identified by biochemical characterization. Organic solvent like Ethanol, Methanol, Acetone, Chloroform and Diethyl-ether was used for the extraction. Antimicrobial assay was done by agar well diffusion method on Mueller-Hinton Agar plates. The extracts of Cymbopogon species were effective against all four pathogens, and C. citratus showed maximum antibacterial activity than other species. Also, Cymbopogon potency was enhanced by methanol extraction which indicates that active material was extracted well in methanol compared to other solvents. These results imply that these medicinal plants can be used as a source of novel drugs for the treatment of infectious diseases caused by pathogenic microorganisms. These three selected Cymbopogon species were characterized by RAPD markers. Dendrogram constructed by cluster analysis of RAPD markers showed that C. martinii and C. citratus are closely related. Since morphological differences among these species are indistinctive, RAPD characterization can be helpful in their Discrimination. Also knowledge of genetic diversity can be used to identify the specific antimicrobial agent in these Cymbopogon species.